Teaching Teachers from Standards to Lessons - Heeringa, Coggin (Proceedings of the Wisconsin Space Conference, 2015)
Funds from Wisconsin Space Grant Consortium were used to provide scholarship stipends to upper elementary and middle school teachers, enabling them to take a continuing education class through the University of Wisconsin-Green Bay Education Outreach Program and/or participate in workshops sponsored by Crossroads at Big Creek. The objective of the class and workshops was to help teachers gain content knowledge and develop lessons aligned with the proposed Next Generation Science Standards.